Benefit accrual with cardiovascular disease prevention and effects of discontinuation: a modelling study. (3rd October 2022) - Wu, R; Williams, C; Zhou, J; Schlackow, I; Emberson, J; Reith, C; Keech, A; Robson, J; Wilkinson, K; Armitage, J; Collins, R; Gray, A; et al.
Abstract: Background: Statin therapy reduces rates of heart attacks and strokes and improves survival in people at increased cardiovascular disease (CVD) risk. However, there is some uncertainty when to start and how long to persist with statin therapy so as to optimise benefits. Purpose: To project the accrual of benefit with statin therapy in population groups by age at therapy initiation using a newly developed micro-simulation model. Methods: Participants without previous CVD (N=44, 412) and with previous CVD (N=13, 061) at entry were randomly selected from the UK Biobank cohort, ensuring sufficient representation in respective categories by age, LDL cholesterol, diabetes and 10-year CVD risk categories (QRISK3 score, for those without previous CVD only). The CTT-UKB model, a CVD micro-simulation model [1], was used to predict subsequent survival and quality-adjusted life years (QALYs) of the participants using their characteristics at entry. Treatment with atorvastatin 40mg daily was used as an example to illustrate the effect of the therapy compared to no such therapy. Scenarios include: (1) lifelong preventive therapy, (2) preventive therapy stopped at 80 years of age, and (3) delayed initiation of preventive therapy by 5 years in participants under 45 years of age. Results: Statin treatment benefits, measured in QALYs gained, accrue over lifetime. The majority of benefits accrue later in life. Men accumulate larger benefits and earlier than women (Figure 1A). The pattern of benefits accrual is similar for participants with and without previous CVD (data not shown). The higher the participants' CVD risk, the larger and earlier the benefits, with younger participants accruing larger benefits (Figure 1B). Compared with lifelong prevention, stopping treatment at 80 years of age leads to large reductions in overall benefits, especially in women and those at lower CVD risk. For example, compared to lifelong therapy, people without previous CVD who initiate therapy in their 50s, would lose 47% of QALYs benefit (if men), 66% (if women), 73% (if with CVD risk <5%), and 35% (if with CVD risk ≥20%), respectively, if they stop treatment when they reach 80 years of age. Five-year delay of statin therapy initiation in people under 45 years of age reduces their benefits by about 4% on average, though the loss is somewhat larger in people at higher CVD risk (Figure 2). Conclusion: Benefits from lifelong cardiovascular prevention accrue over peoples' lifespan with large share of benefits accruing at older age. Stopping treatment earlier substantially reduces benefits. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): UK NationalInstitute for Health Research (NIHR) Health Technology Assessment (HTA) Programme, UK Medical Research Council (MRC), and British Heart Foundation